Age, chemistry, and tectonic setting of Miramichi terrane (Early Paleozoic) volcanic rocks, eastern and east-central Maine, USA - Ludman, Allan; McFarlane, Christopher; Whittaker, Amber T.H. (Atlantic Geoscience, 2021)
Volcanic rocks in the Miramichi inlier in Maine occur in two areas separated by the Bottle Lake plutonic complex: the Danforth segment (Stetson Mountain Formation) north of the complex and Greenfield segment to the south (Olamon Stream Formation). Both suites are dominantly pyroclastic, with abundant andesite, dacite, and rhyolite tuffs and subordinate lavas, breccias, and agglomerates. Rare basaltic tuffs and a small area of basaltic tuffs, agglomerates, and lavas are restricted to the Greenfield segment. U–Pb zircon geochronology dates Greenfield segment volcanism at ca. 469 Ma, the Floian–Dapingian boundary between the Lower and Middle Ordovician. Chemical analyses reveal a calc-alkaline suite erupted in a continental volcanic arc, either the Meductic or earliest Balmoral phase of Popelogan arc activity. The Maine Miramichi volcanic rocks are most likely correlative with the Meductic Group volcanic suite in west-central New Brunswick. Orogen-parallel lithologic and chemical variations from New Brunswick to east-central Maine may result from eruptions at different volcanic centers. The bimodal Poplar Mountain volcanic suite at the Maine–New Brunswick border is 10–20 myr younger than the Miramichi volcanic rocks and more likely an early phase of back-arc basin rifting than a late-stage Meductic phase event. Coeval calc-alkaline arc volcanism in the Miramichi, Weeksboro–Lunksoos Lake, and Munsungun Cambrian–Ordovician inliers in Maine is not consistent with tectonic models involving northwestward migration of arc volcanism. This >150 km span cannot be explained by a single east-facing subduction zone, suggesting more than one subduction zone/arc complex in the region.